Teaching and learning in Icelandic and Science in the context of national tests in Iceland: A conceptual model of curriculum teaching and learning - Runar Sigthorsson (University College London, 2008)
The paper presents a curriculum model used as a theoretical framework to analyse classroom practice in Icelandic and Science in the context of national tests in Iceland. The model represents a synthesis of literature about curriculum, teachers’ conceptions, pedagogical content knowledge, teaching and learning and assessment. The curriculum model comprises three main aspects of curriculum: the intended, the implemented and the attained curriculum. Each aspect includes several ‘frames’ or areas that can be studied separately, together or in interaction with one another. Furthermore theories of teachers’ conceptions, pedagogical content knowledge and perceived self- and collective efficacy are used to analyse the possible discrepancy between the curriculum aspects and the effects of national tests on the implemented and attained curricula.